Host Respiratory Transcriptome Signature Associated with Poor Outcome in Children with Influenza–Staphylococcus aureus Pneumonia . (28th July 2022) - Britto, Carl; Mohorianu, Irina; Yeung, Tracy; Cheung, Elaine; Novak, Tanya; Hall, Mark W; Mourani, Peter M; Weiss, Scott L; Thomas, Neal J; Markovitz, Barry; Randolph, Adrienne G; Moffitt, Kristin L
Abstract: Respiratory coinfection of influenza with Staphylococcus aureus often causes severe disease; methicillin-resistant S. aureus (MRSA) coinfection is frequently fatal. Understanding disease pathogenesis may inform therapies. We aimed to identify host and pathogen transcriptomic (messenger RNA) signatures from the respiratory compartment of pediatric patients critically ill with influenza– S. aureus coinfection (ISAC), signatures that predict worse outcomes. Messenger RNA extracted from endotracheal aspirate samples was evaluated for S. aureus and host transcriptomic biosignatures. Influenza-MRSA outcomes were worse, but of 190 S. aureus virulence-associated genes, 6 were differentially expressed between MRSA-coinfected versus methicillin-susceptible S. aureus –coinfected patients, and none discriminated outcome. Host gene expression in patients with ISAC was compared with that in patients with influenza infection alone. Patients with poor clinical outcomes (death or prolonged multiorgan dysfunction) had relatively reduced expression of interferons and down-regulation of interferon γ–induced immune cell chemoattractants CXCL10 and CXCL11. In ISAC, airway host but not pathogen gene expression profiles predicted worse clinical outcomes. Abstract : Staphylococcus aureus coinfection is associated with worse outcomes in severe influenza, but the associated pathophysiology is poorly understood. Evaluation of bacterial and host transcriptomes from airways early in illness could identify pathways to target to improve outcomes.